Comprehensive Analysis of Leadership Strategies for Workforce Retention in the Service Sector - Marquardt, Mariam - Arem (Digital Repository of Theses, 2026)
Workforce retention remains challenging in today’s service industry, where high turnover negatively impacts productivity, culture, and profitability. This research investigates how leadership influences retention in the service sector and fills an empirical gap in high-confidence, sector-specific research in quantitative studies on turnover-minimising leadership strategies. Drawing on a range of literature, the study examines how factors, such as adaptive leadership, workplace community membership, and feedback frequency, predict employee retention (ER). A cross-sectional survey of service-sector employees (n = 389) was analysed using descriptive and inferential statistics, including Kendall’s tau-b correlations and regression at a 95% confidence level. Correlation analyses revealed weak but consistent positive associations between adaptive leadership and ER, as well as between leadership-promoted workplace community membership and ER. Simple regressions confirmed both adaptiveness and belonging as significant predictors of the retention composite. In the multiple regression model, adaptiveness emerged as the strongest predictor (β = .24, p < .001), while feedback frequency also demonstrated a smaller yet significant effect (β = .12, p = .023). While belonging was a significant predictor in the simple regression, it lost significance when adaptive leadership and feedback were included in the multiple regression model (R² = .111). The findings provide quantitative evidence that adaptive leadership, supported by regular, constructive feedback, is most strongly associated with ER in service firms. These results contribute to the understanding of leadership’s role in reducing turnover and offer practical insights for developing effective retention strategies in the service sector.